PEMBERDAYAAN KELUARGA LANSIA MELALUI PROGRAM BINA KELUARGA LANSIA (BKL) DI KAMPAR - Muhammad Haris; Moralely Hendrayani; Halma Nurhijjah (Universitas Islam Negeri Imam Bonjol Padang, 2023)
The purpose of this study was to find out the activities of religious coaching, physical coaching, psychological/mental coaching, and socio-economic coaching in Limau Manis Village, Kampar District, Kampar Regency in implementing the BKL program in Limau Manis village, as well as knowing the success and benefits of the BKL program coaching for families who have elderly. This study uses a qualitative research method that focuses on in-depth observations, so that the results of the study on the problems studied are more comprehensive. The results of the study show that religious development activities are carried out in the form of worship such as prayer and reading the Qur'an as well as awareness raising in the form of routine recitations carried out with the family. Physical development is carried out in the form of sports with other elderly people and also the family in order to get a fit body. Mental coaching is carried out in the form of raising awareness and training for families about the need for care for the elderly who need love. Families are nurtured with elderly care activities. Then social economic development, namely by practicing craft businesses by the elderly and their families, and the family must support financially whatever the elderly want because indeed the elderly like to be given financial support so they feel important in the midst of many people